EVALUATION THE EFFECTS OF HARVEST STAGE AND SOME POSTHARVEST TREATMENTS ON QUALITY OF BEACH FRUIT CV. "Dixired" DURING COLD STORAGE - Al-Bamarny, Sarfaraz F.; Ahmed, Tahir A. (Diyala Agricultural Sciences Journal, 2017)
The fruits source of this study was a commercial orchard of peach Dixired cv. located at Sartang village in Semel- Duhok- Kurdistan Region-Iraq, during growing season (2012). Harvested fruit transferred to central laboratory of Agriculture College - Duhok University, to study the effect of harvest stage (first harvest stage at35% red color and second harvest stage at 75% red color) and dipped in water at room temperature (24˚C) as control, 45, 55˚C and 2% fungicide (Bravo) for two minutes then stored in cold storage at 0±1˚C and 85-90% RH for 25 and 55 days period on quality of peach fruit during cold storage. The results revealed that peach fruit harvested at second harvest stage had significantly lower fruit firmness, titratable acidity, higher vitamin C, total sugar, juice % and decay as compared with first harvest stage. Peach fruit dipped at 45 and 55˚C hot waterrecorded significantly the higher weight loss in compression with control; fruit of postharvest treatment had a significant increase in fruit firmness total acidity and decrease in fruit decay compared to control. Fruit dipped in hot water at 55˚Cand 2% fungicide had a significant increase in fruit vitamin C and total sugar content. The interaction between factors under the study had significantly positive effect on most storage characteristic especially fruit firmness, TA, vitamin C, and decay.